Analysis of Database of University Examination System: A Case Study - Singh, Balvir; Singh, AJ; Chauhan, Rajesh (International Journal of Computer Sciences and Engineering, 2025)
The database of information system of any organization store crucial information. Organizations are considering this stored information as asset, because the information provided by the organization's information system play an important role in its functioning and also in the decision making processes. Depending on the availability of quality of information, administrative authorities of organization can take right decision for its stakeholders and for its better functioning. Keeping this in mind, present paper analysed the database of the University Examination System of Himachal Pradesh University. Data stored in the database of examination system is analysed and number of discrepancies are revealed in the data. There is lot of redundant and inconsistent data stored in the examination database. Upon analysing the data, it was found that there are number of fields in the database that store the redundant data, significant number fields are found empty besides, few constraints has been enforced on the majority of data. Poor database design is one of many factor that contributes to such problems. This paper also analyses the structure of relational table that lead to database of University Examination system and in the last highlight the findings of analysis.